REPRESENTASI TOXIC MASCULINITY PADA FILM “NANTI KITA CERITA TENTANG HARI INI (NKCTHI)” - Agusman Wahyudi; Anis Endang SM; Bayu Risdiyanto (Jurnal Komunikasi dan Budaya, 2022)
in social life. The social system and structure attached to the concept of masculinity is motivated by the ideology of patriarchy and capitalism, causing the phenomenon of toxic masculinity and placing men in an upper and superior position. The purpose of this research is to reveal and get a representation of the toxic masculinity of a film. The representation of toxic masculinity has been socialized, constructed, and strengthened by a film. This research is a qualitative research with Roland Barthes semiotic analysis approach using critical paradigm with masculinity theory approach, toxic masculinity concept, and film as social reality in order to get a representation of toxic masculinity concept. The results of this study indicate that men are displayed according to social construction according to the patriarchal system, where the construction of men should not show emotions and men show anger. In addition to the patriarchal system, the ideology of capitalism is another ideology that influences the depiction of masculine men.